Acute seizures attributable to falciparum malaria in an endemic area on the Kenyan coast. - Kariuki, S; Ikumi, M; Ojal, J; Sadarangani, M; Idro, R; Olotu, A; Bejon, P; Berkley, J; Marsh, K; Newton, C (2011)
Falciparum malaria is an important cause of acute symptomatic seizures in children admitted to hospitals in sub-Saharan Africa, and these seizures are associated with neurological disabilities and epilepsy. However, it is difficult to determine the proportion of seizures attributable to malaria in endemic areas since a significant proportion of asymptomatic children have malaria parasitaemia. We studied children aged 0-13 years who had been admitted with a history of seizures to a rural Kenyan hospital between 2002 and 2008. We examined the changes in the incidence of seizures with the reduction of malaria. Logistic regression was used to model malaria-attributable fractions for seizures (the proportion of seizures caused by malaria) to determine if the observed decrease in acute symptomatic seizures was a measure of seizures that are attributable to malaria. The overall incidence of acute symptomatic seizures over the period was 651/100,000/year (95% confidence interval 632-670) and it was 400/100,000/year (95% confidence interval 385-415) for acute complex symptomatic seizures (convulsive status epilepticus, repetitive or focal) and 163/100,000/year (95% confidence interval 154-173) for febrile seizures. From 2002 to 2008, the incidence of all acute symptomatic seizures decreased by 809/100,000/year (69.2%) with 93.1% of this decrease in malaria-associated seizures. The decrease in the incidence of acute complex symptomatic seizures during the period was 111/100,000/year (57.2%) for convulsive status epilepticus, 440/100,000/year (73.7%) for repetitive seizures and 153/100,000/year (80.5%) for focal seizures. The adjusted malaria-attributable fractions for seizures with parasitaemia were 92.9% (95% confidence interval 90.4-95.1%) for all acute symptomatic seizures, 92.9% (95% confidence interval 89.4-95.5%) for convulsive status epilepticus, 93.6% (95% confidence interval 90.9-95.9%) for repetitive seizures and 91.8% (95% confidence interval 85.6-95.5%) for focal seizures. The adjusted malaria-attributable fractions for seizures in children above 6 months of age decreased with age. The observed decrease in all acute symptomatic seizures (809/100 000/year) was similar to the predicted decline (794/100,000/year) estimated by malaria-attributable fractions at the beginning of the study. In endemic areas, falciparum malaria is the most common cause of seizures and the risk for seizures in malaria decreases with age. The reduction in malaria has decreased the burden of seizures that are attributable to malaria and this could lead to reduced neurological disabilities and epilepsy in the area.